A study of contrast sensitivity changes in normal individual and diabetic patients with and without diabetic retinopathy - Noticewala, Vaibhavee; Shastri, Manisha (International Journal of Research in Medical Sciences, 2017)
Background: To study contrast sensitivity changes in healthy individuals and in diabetic patients with and without diabetic retinopathy. Methods: Study was conducted at tertiary care hospital, Surat. Contrast sensitivity functions were assessed with PELLI ROBSON CHART with help of electronic displays. Results were analyzed using chi square test. Results: Total 114 patients were taken into study. Maximum patients were in age group 46-55 years. Mean age of diabetic individuals was 51 and in healthy individual mean age is 52. Total 18 patients with Diabetic retinopathy, among 57 diabetic patients were taken into study. Sex ratio in diabetic group is Male: Female 2.5:1 and healthy individual is Male: Female 2.1:1. There is significant reduction in contrast sensitivity function in subjects with diabetes as compared to healthy individuals. (P value<0.05) There is significant reduction in Visual Acuity (P value<0.05). There was significant association of high FBS and PP2BS level with diabetic retinopathy and contrast sensitivity, the contrast sensitivity function decreases as metabolic control of blood sugar level fluctuates. In present study, Duration of diabetes mellitus doesn’t have significant association with contrast sensitivity function. (p value > 0.05) In present study, there isn’t significant association of contrast sensitivity function and visual acuity with cataract, as above patients were having early or few cataract changes. (p value > 0.05). In present study, there isn’t significant association between blood pressure control and contrast sensitivity function (p value > 0.05). Conclusions: Majority of the subjects in the present study belonged to the age group 46-55 years (38.6%). Mean age of diabetic individuals was 51 and healthy individual mean age is 52. Total 18 patients with DR, among 57 diabetic patients were taken into study. Sex ratio (male: female) in diabetic group is 2.5:1 and healthy individual is 2.1:1. There is significant reduction in contrast sensitivity function in subjects with diabetes as compared to healthy individuals. (P value<0.05). So is with decimal equivalent VA and decimal equivalent BCVA. (Both P value<0.05). There is significant association between FBS and PP2BS level with contrast sensitivity, the contrast sensitivity function decreases as metabolic control of blood sugar level fluctuates. (P value< 0.05). There was significant association between high FBS level and diabetic retinopathy as well. (p value<0.05).